Sastra Islami Kontemporer Najîb al-Kilânî dalam Memahami Manusia - Zuriyati Zuriyati (Postgraduate Studies of Universitas Islam Negeri Sunan Ampel Surabaya, Indonesia, 2011)
The object of this paper is man in the modern Islamic literature. The man that it deals with is a modern man, a man overwhelmed by psychological deceases ranging from loneliness, sadness, depression, and the likes. The paper maintains first and foremost that modernity has brought about a serious challenge for modern man. The high standard of living, the demands of life, and the competition among individuals have all been a source for the deepening malaises of the modern man. All this, the paper argues has been reflected in the contemporary Islamic literature whose vibrant expression of modern life has stood a strong indication of the plight of modern man. Contemporary Islamic literature in other words, is the medium through which we can understand the dilemma of modern man as well as the medium through which modern men can resort to express their feeling and live-experience. By Islamic literature we mean any literature that has an ontic and epistemic relationship with the authoritative sources of Islam.